2013
DOI: 10.1016/j.jtcvs.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Temporary biventricular pacing decreases the vasoactive-inotropic score after cardiac surgery: A substudy of a randomized clinical trial

Abstract: Objective Vasoactive medications improve hemodynamics after cardiac surgery but are associated with high metabolic and arrhythmic burdens. The vasoactive-inotropic score was developed to quantify vasoactive and inotropic support after cardiac surgery in pediatric patients but might similarly be useful in adults. Accordingly, we examined the time course of this score in a substudy of the Biventricular Pacing After Cardiac Surgery trial. We hypothesized that the score would be lower in patients randomized to biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 22 publications
(26 reference statements)
1
37
0
1
Order By: Relevance
“…We have previously demonstrated decreasing vasoactive inotropic score and increased urine output with BiVP during phases I and II [33]. As yet unpublished observations of decreasing intrinsic heart rate in the BiVP group further suggest that pacing might suppress atrial and ventricular arrhythmias in the postoperative period.…”
Section: Commentmentioning
confidence: 83%
See 1 more Smart Citation
“…We have previously demonstrated decreasing vasoactive inotropic score and increased urine output with BiVP during phases I and II [33]. As yet unpublished observations of decreasing intrinsic heart rate in the BiVP group further suggest that pacing might suppress atrial and ventricular arrhythmias in the postoperative period.…”
Section: Commentmentioning
confidence: 83%
“…Optimization was similar to phase I, with testing intervals increased to 20 seconds [4]. The newly optimized protocol was then applied to BiVP patients [4,33] until phase III on the first postoperative day. The clinical endpoint, cardiac index, was measured by thermal dilution immediately prior to phase III testing.…”
Section: Methodsmentioning
confidence: 99%
“…At our center, clinical trials conducted with adult patients at risk for left ventricular dysfunction showed that temporary BiVP increased urine output and reduced the vasoactive-inotropic score (VIS) during 3 h immediately after cardiopulmonary bypass (CPB) [11]. Our trial also demonstrated the hemodynamic benefits of atrioventricular delay (AVD) and interventricular delay optimization [14, 17].…”
Section: Introductionmentioning
confidence: 75%
“…A previous substudy from the BiPACS trial demonstrated reduced VIS in BiVP patients over 3 hours after CPB. 19 How hemodynamics would influence the administration of vasoactive agents is undefined, however, and administration of these drugs is not regulated by protocol at Columbia. 19 The present analysis demonstrates no significant difference in VIS between BiVP and SOC patients in phase III.…”
Section: Discussionmentioning
confidence: 99%
“…19 How hemodynamics would influence the administration of vasoactive agents is undefined, however, and administration of these drugs is not regulated by protocol at Columbia. 19 The present analysis demonstrates no significant difference in VIS between BiVP and SOC patients in phase III. Heart rate differences in phase III, therefore, probably do not reflect differences in vasoactive medication doses, although a small trend to decreased VIS in the BiVP group is present.…”
Section: Discussionmentioning
confidence: 99%